Composition of clastic sediments in the Somosaguas area (middle Miocene, Madrid Basin): insights into provenance and palaeoclimate - Fesharaki, Omid; Arribas, José; López Martínez, N. (Journal of Iberian Geology, 2015)
The western area of the Cenozoic Madrid Basin has not been adequately studied. This, combined with the high homogeneity of detrital facies makes the stratigraphic correlation with other areas of the basin rather difficult. Consequently, only a detailed characterization of different study zones can allow subsequent correlation over this area. Over the last years there have been discovered several vertebrate fossil sites in this area that allow the dating of the sediments which host the fossil remains and provide data about palaeoclimatic trends. In this paper we present the results of the light minerals petrographic analysis carried out in one of these sites (Somosaguas paleontological site). Previous palaeontological and isotopic studies in this site indicate a climate event of cooling and rising aridity that has been described globally for the period after the Miocene Climatic Optimum. The petrographic data and indices presented here corroborate this trend towards a more arid climate through the Somosaguas sedimentary succession. Besides we study the grades of alteration of plagioclase grains as a proxy in the evaluation of palaeoclimatic variations. The increase towards the top of the succession of less altered plagioclase grains suggests a decrease in precipitations and thus more aridity. Part of the quartz and K-feldspar grains display several features like embayments and alterations pointing to palaeosoils formation and reworking processes. These characteristics and other observations suggest several sedimentary pulses in a geotectonic setting of “basement uplift” and a mixed lithological provenance for the Somosaguas deposits (granites, gneisses and minor quantities of low-grade metamorphic rocks).